Threats to the economic security of subjects of logistics activities in the current conditions and means of their leveling - Vivchar, Oksana; Shatarskyi, Artur; Balko, Dmytro (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article focuses on the problem of guaranteeing the stable long-term functioning of enterprises in the field of logistics. It is pointed out that economic security in the environment of critically acute challenges of war and the socio-economic instability caused by it becomes a leading function in the sense of preserving the viability of enterprises and organizations, including logistics ones. It is shown that today, for such purposes, enterprises organize their own effective safety-oriented activities. Therefore, the purpose of the study was to identify threats to the economic security of logistics entities in modern conditions and to substantiate the means of their leveling. Risks and threats to the economic security of business entities specializing in logistics services have been identified. A toolkit for effective security-oriented activities of logistics enterprises has been developed, the implementation of which will improve activities to guarantee their economic security, and, therefore, risk resistance and stability of functioning and development. It has been proven that effective security-oriented management begins with the identification of threats to the economic security of logistics entities. According to the results of the analysis of the specifics and modern business conditions of domestic subjects in the field of logistics, it was established that the main threats, which should be countered by active activity in this area, are the negative consequences of the destabilization of the domestic market in war conditions, which lead to decapitalization, deterioration of financial results, receiving losses, bankruptcy, unprofitability of investment projects, use of morally and physically outdated technologies, low level of intellectual and personnel support, narrowing of the domestic market and loss of customers and income, cyber crimes, destruction of logistics infrastructure, etc. It is substantiated that on the basis of taking into account these challenges, logistics entities should implement a balanced set of measures aimed at strengthening the foundations of financial security (formation of insurance and reserve funds; quality management and insurance of financial risks; more thorough financial forecasting and planning; conclusion of long-term contracts diversification of sources of formation and distribution of financial flows), improvement of the technical-technological system (modernization of the technical-technological and material-technical base of the logistics economy; active innovative activity, investment in research and development, implementation of innovations; active and productive activity on the market of intellectual property objects), development of intellectual and personnel support ( increasing and effective use of human resources, development and improvement of the staff’s qualifications, improvement of the work motivation system), improvement of activities on the market (active activities in marketing market research; cooperation with foreign partners; investments in the development of logistics infrastructure; improvement of own marketing activities), strengthening of the information field of security (cooperation with ICT entities in the field of digitalization of business processes and strengthening of information hygiene , ensuring the information security of the enterprise and its counterparties), improvement of force security (insurance of military risks; increase of costs for security and legal support of business; implementation of active economic intelligence, improvement of the internal system of protection against economic espionage; cooperation with leading market agents in the field of force security) of the business entity.